2015
DOI: 10.1088/0022-3727/48/3/035106
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental insights into the threshold characteristics of organic field-effect transistors

Abstract: We physically model the threshold characteristics of organic field-effect transistors (OFETs) using a two-dimensional finite-element method. The transfer characteristics are simulated for staggered OFETs with various electronic structures. A reliable method to extract a structureunique threshold voltage is presented based on the second-derivative method. By changing the hole injection barrier height in such a manner that the flat-band voltage, defined from the difference of Fermi levels of gate and source elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
(35 reference statements)
3
20
0
Order By: Relevance
“…As will be shown later, the metal-insulator-metal model is completely valid for ORDs with GDOS as long as the effective injection barrier height is higher than about 0.2 eV. This recalls the same behaviour of M/O junctions in organic diodes and field-effect transistors in which organic semiconductor was assumed perfectly crystalline [35,40].…”
Section: Potential Distributionsupporting
confidence: 54%
“…As will be shown later, the metal-insulator-metal model is completely valid for ORDs with GDOS as long as the effective injection barrier height is higher than about 0.2 eV. This recalls the same behaviour of M/O junctions in organic diodes and field-effect transistors in which organic semiconductor was assumed perfectly crystalline [35,40].…”
Section: Potential Distributionsupporting
confidence: 54%
“…As a result, by adjusting the proportions of these compounds continuous tuning of the transistor threshold voltage is possible. Intriguingly, since most OFETs operate only in accumulation mode, V TH should be in principle zero [38].…”
Section: Resultsmentioning
confidence: 99%
“…Typical values for σ DOS can be on the order of 0.25 eV, a not‐inconsequential fraction of the ideal Schottky barrier for a typical metal–organic semiconductor interface. Using PES measurements of the HOMO and LUMO levels, Jung et al observed that the σ DOS creates an effective HOMO (LUMO) level that is located within the bandgap, at higher (lower) levels than the peak of the HOMO (LUMO) distribution . According to Equations and , φ B is then decreased when compared to calculations using values of EA obtained from the HOMO peak according to the offset values for EA and IE due to the spread of energy levels into the gap.…”
Section: Charge Injection Through a Metal–semiconductor Interfacementioning
confidence: 99%